The Impact of Schools’ Closure on the Vulnerable to Learn and Study Remotely - Abdelbasit Gadour (BIRCU, 2021)
In searching the literature on the impact of COVID-19 on children’s education very little attention has been given to the effect of schools-closure on children with special educational needs (SEN). Supporting SEN children during such difficult times is clearly important but the best way of achieving this is currently unclear. In fact, the support available falls short to meet the educational needs of those capable to learn, let alone those who find it difficult to learn. In response to the needs for education, all developed countries made sure that learning fully continued taking place online as schools provided remote schooling, however the same cannot be found in developing countries e.g. Libya and consequently children with SEN have suffered the most. Currently, all the burden is placed on parents to support children at home during such challenging time. Thus, the intention in this study is to gain a better understanding of how children are supported at home during the closure of schools with special reference to those who have already found it difficult to learn. 49 parents agree to take part in online survey concerned with SEN children learning at home and the challenges experienced. The results of this study suggested online learning is not straightforward and in particular with SEN children. The majority of parents in this study found it extremely hard to respond to the needs of SEN children at home without the support and advice of school’s professionals. There is certainly a need for more educational resources and effective online learning strategies to support both children and parents.